TWIST1-EP300 Expedites Gastric Cancer Cell Resistance to Apatinib by Activating the Expression of COL1A2 - Gang Yu; Wanjing Chen; Xianghua Li; Liang Yu; Yanyan Xu; Qiang Ruan; Yawei He; Yong Wang (Analytical Cellular Pathology)
The association between collagen type I alpha (COL1A) and chemoresistance has been verified in cancers. However, the specific role of COL1A2 in gastric cancer (GC) cell resistance to apatinib, a highly selective small-molecule inhibitor of vascular endothelial growth factor receptor 2, has not been investigated before. The purpose of this study was to explore the potential factors associated with COL1A2 regulation on GC cell apatinib resistance in vitro. With the aid of the Oncomine database and integrated bioinformatics methods, we identified COL1A2 overexpression in GC and its prognostic value. Mechanistically, the COL1A2 promoter has a distinct H3K27ac modification site and that E1A binding protein p300 (EP300) and twist family bHLH transcription factor 1 (TWIST1) can bind to the COL1A2 promoter, which in turn transcriptionally activated COL1A2 expression. In addition, overexpression of COL1A2 significantly promoted resistance to apatinib in GC cells, but knockdown of EP300 or TWIST1 remarkably inhibited COL1A2 expression and promoted sensitivity of GC cells to apatinib. Our findings demonstrated that the combination of EP300 and TWIST1 has a synergistically regulatory effect on COL1A2 expression, thus contributing to apatinib resistance in GC cells.